Answer:
The final temperature is the sum of the initial temperature and the change in temperature. The initial temperature is 102°F. The change in temperature is -3°F.
Operation:
102°F + (-3°F) = (102 - 3)°F = 99°F
Step-by-step explanation:
Answer:
y= 4/5x + 1
Step-by-step explanation:
Answer:
2
Step-by-step explanation:
This expression can be rewritten as
8
----
9
======
4
---
9
If we now invert the denominator fraction 4/9 and multiply the result, we get:
8 9
----- * ----- = 2
9 4
Answer:
im pretty sure the answer would be 40m
Step-by-step explanation: